TRANSFORMASI PENDIDIKAN TINGGI DALAM MEMPERSIAPKAN SDM ADMINISTRASI PERKANTORAN YANG KOMPETEN UNTUK INDONESIA EMAS 2045 - Dyah Bayu Framesthi; Delia Subrayanti (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Higher education plays a crucial role in shaping competent human resources to face global challenges and achieve the vision of Indonesia Emas 2045. The Office Administration study program must adapt to technological advancements, digitalization, and changing workplace dynamics. The transformation of higher education in this field includes enhancing skill-based curricula, integrating technology into administrative processes, and strengthening soft skills such as communication, leadership, and organizational management. This article explores how higher education, particularly in Office Administration, contributes to preparing professional, adaptive, and highly competitive graduates in the digital era. Through literature analysis and case studies, it is found that curriculum innovation, industry collaboration, and the utilization of modern technology are key factors in producing graduates ready to contribute to national development. Thus, the transformation of higher education in Office Administration is essential in shaping excellent human resources that support the vision of Indonesia Emas 2045.